Effects of Yogic Interventions on Patients Diagnosed With Cardiac Diseases. A Systematic Review and Meta-Analysis - Kalra, Sheetal; Miraj, Mohammad; Ajmera, Puneeta; Shaik, Riyaz Ahamad; Seyam, Mohamed K.; Shawky, Ghada M.; Alasiry, Sharifa M.; Mohamed, Elsayed H.; Alasiri, Hatim M.; Alzhrani, Msaad; Alanazi, Ahmad; Alqahtani, Mazen; et al. (Frontiers in Cardiovascular Medicine, 2022)
Abstract Objective Presently, evidence-based researches regarding the efficacy of complimentary therapies like yoga for patients with different cardiac diseases are limited and conflicting. Objective of the present study is to conduct a systematic review and meta-analysis of randomized controlled trials (RCTs) on yogic interventions compared with usual care or non-pharmacological treatment in patients with diagnosed cardiac diseases. Methods We conducted an electronic search of literature published from 2006 toMay 2021 through five databases.PRISMA statement was used for to develop and report systematic review and Meta-analysis protocol. 16 RCTs were included in systematic review and 11 RCTs were used for meta-analysis.Outcome measures were blood pressure, lipid profile and psychosocial measures. Cochrane collaboration tool was used to assess bias risk. Results Results show that yogic interventions resulted in significant reduction in Systolic (d= 0.46, 95% CI 0.08 – 0.84, I2 =81.86%) and Diastolic blood pressure (d= 0.56, 95% CI 0.13 – 0.99, I2 =84.84%). Amedium statistically significant increase of HDL (d= 0.67, 95% CI 0 to 1.33, I2 79.7%) and low but significant effect on LDL (d= 0.23, 95% CI -0.08- 0.54, I2 32.61%), total cholesterol (d= 0.28, 95% CI -0.14- 0.70, I2 63.72%), and triglycerides (d= 0.43, 95% CI -0.10 – 0.97, I2 76.64% was observed.Pooled effect sizes showed medium to low statistically significant effect on psychosocial indicators viz. QoL, stress, anxiety and depression. Conclusion Meta-analysis found strong evidence of effectiveness of yogic interventions on lipid profile, blood pressure and psychosocial outcomes in patients with diagnosed cardiac diseases.